Clero e família: os notários e comissários do Santo Oficio no Sul de Portugal (o caso de Beja na primeira metade do século XVIII) - Fernanda Olival (Nuevo mundo - Mundos Nuevos, 2008)
The first aim of this paper is to analyze in comparative way the correlation between the number of commissioners of the Holy Office at Beja and diverse topics: demography, degree of repression exerted by the Inquisition, proximity of the border with Castile, statute of the locality. Secondly, because all the previous hypotheses are insufficient to explain the scarce number of commissioners and notaries at Beja, we try to study the profile of the clergymen who had been in these posts and those who had disapproved in the candidacy. The majority of them that was born at Beja had difficulties in obtaining the post because they are from new–Christians families, although their family try to make them commissioners. At this town even for those that were born outside it was not easy.